Question
upstudy study bank question image url

(d) Suppose that a cell dehydration model satisfies the differential equation, \[ \frac{d W}{d t}=-k W^{\frac{2}{3}} \] Assume that the volume of water in the cell initially is \( W(0)=8 \mathrm{~mm}^{3} \). Also, assume that the volume of water has decreased to \( W(6)=1 \mathrm{~mm}^{3} \) after 6 hours. (i) Solve the differential equation by separating like variables. (ii) Determine the value of k and the time when the cell will be completely dry.

Ask by Park West. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solution to the differential equation is: \[ W(t) = \left(\frac{6 - k t}{3}\right)^3 \quad \text{mm}^3 \]

Solution

### Problem (d)(i): Solving the Differential Equation by Separating Variables We are given the differential equation governing the volume of water \( W(t) \) in a cell: \[ \frac{dW}{dt} = -k W^{\frac{2}{3}} \] with the initial condition \( W(0) = 8 \, \text{mm}^3 \). **Step 1: Separate Variables** To solve the differential equation, we separate the variables \( W \) and \( t \): \[ \frac{dW}{W^{\frac{2}{3}}} = -k \, dt \] **Step 2: Integrate Both Sides** Next, we integrate both sides of the equation: \[ \int W^{-\frac{2}{3}} \, dW = \int -k \, dt \] **Integral on the Left Side:** \[ \int W^{-\frac{2}{3}} \, dW = \frac{3}{1} W^{\frac{1}{3}} + C_1 = 3 W^{\frac{1}{3}} + C_1 \] **Integral on the Right Side:** \[ \int -k \, dt = -k t + C_2 \] Combining both integrals: \[ 3 W^{\frac{1}{3}} + C_1 = -k t + C_2 \] For simplicity, let \( C = C_2 - C_1 \): \[ 3 W^{\frac{1}{3}} = -k t + C \] **Step 3: Apply Initial Condition** Using the initial condition \( W(0) = 8 \, \text{mm}^3 \): \[ 3 (8)^{\frac{1}{3}} = 3 \times 2 = 6 = -k \times 0 + C \implies C = 6 \] **Step 4: Solve for \( W(t) \)** Substituting \( C = 6 \) into the equation: \[ 3 W^{\frac{1}{3}} = 6 - k t \] Divide both sides by 3: \[ W^{\frac{1}{3}} = \frac{6 - k t}{3} = 2 - \frac{k t}{3} \] Cubing both sides to solve for \( W(t) \): \[ W(t) = \left(2 - \frac{k t}{3}\right)^3 \] **Final Solution:** \[ W(t) = \left(2 - \frac{k t}{3}\right)^3 \quad \text{mm}^3 \] Alternatively, it can be written as: \[ W(t) = \left(\frac{6 - k t}{3}\right)^3 \quad \text{mm}^3 \] Both forms are equivalent and valid representations of the solution. ### Answer Problem i Answer: After separating and integrating, a general solution is  W(t) = [(6 – k t) ⁄ 3]³. Thus,  W(t) = ((6 − kt)/3)^3 mm³.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the differential equation \[ \frac{d W}{d t} = -k W^{\frac{2}{3}}, \] we will begin by separating the variables. This involves rearranging the equation to isolate \( W \) and \( t \) on opposite sides: \[ \frac{d W}{W^{\frac{2}{3}}} = -k dt. \] Next, we integrate both sides. The left side will be integrated with respect to \( W \), and the right side with respect to \( t \): \[ \int W^{-\frac{2}{3}} dW = \int -k dt. \] The left integral evaluates to: \[ \frac{W^{\frac{1}{3}}}{\frac{1}{3}} = 3W^{\frac{1}{3}} + C_1, \] and the right evaluates to: \[ -k t + C_2. \] Setting both results equal gives us: \[ 3W^{\frac{1}{3}} = -kt + C. \] Now let's solve for \( W \) from the equation above: \[ W^{\frac{1}{3}} = \frac{-kt + C}{3}. \] Cubing both sides, we find \[ W = \left(\frac{-kt + C}{3}\right)^{3}. \] Next, we need to find the constants using the initial conditions provided: \( W(0) = 8 \) and \( W(6) = 1 \). Using the first condition, we input \( t = 0 \): \[ 8 = \left(\frac{C}{3}\right)^3. \] So, \[ C = 3 \cdot 8^{\frac{1}{3}} = 3 \cdot 2 = 6. \] Next, we use the second condition \( W(6) = 1 \): \[ 1 = \left(\frac{-6k + 6}{3}\right)^{3}. \] Taking the cube root gives: \[ 1 = \frac{-6k + 6}{3} \Rightarrow -6k + 6 = 3 \Rightarrow -6k = -3 \Rightarrow k = \frac{1}{2}. \] With \( k \) found, our expression for \( W \) becomes: \[ W = \left(\frac{-\frac{1}{2} t + 6}{3}\right)^{3}. \] To find when the cell will be completely dry, we set \( W = 0 \): \[ \frac{-\frac{1}{2} t + 6}{3} = 0 \Rightarrow -\frac{1}{2} t + 6 = 0 \Rightarrow t = 12. \] Thus, the cell will be dry after 12 hours. In summary: (i) Solution is \[ W = \left(\frac{-\frac{1}{2} t + 6}{3}\right)^{3}. \] (ii) Value of \( k \) is \( \frac{1}{2} \), and the cell will be completely dry at \( t = 12 \) hours.

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy